Supply Chain Management Improvement in Kazakhstan E-Commerce - Bulent Sen; Serikbay Ydyrys; Aizhan Omarova; Malike Munassipova; Almas Kuralbayev (International Journal of Supply Chain Management, 2020)
Abstract— Electronic commerce is widely considered as a part of electronic business and the result of digital transformation. This paper aims to evaluate the capabilities and development of digital technologies in supply chain management. The evaluation process is conducted on the example of Kazakhstan by comparing the country with logistics and digital adaptation leaders. The paper analyses the effectiveness of information, communication, and logistics technologies development in supply chain management (SCM). The analysis involves systematizing secondary information. This research uses statistics from open sources as a foundation for descriptive comparative analysis to achieve research goals. The indicators such as logistics performance and the spread of information and communication technologies are selected for the evaluation. The paper outlines that an effective supply chain is essential to country’s development and integration into the world economy within the context of globalization and digital transformation.